A therapeutic renaissance: emergence of novel targeted agents for metastatic melanoma. (September 2012) - Cowey, C Lance
The therapeutic landscape of metastatic melanoma has recently moved from the dark ages to a period of renewed hope. Until recently, treatment options for patients with this devastating disease have had limited activity with no therapy resulting in an improvement in survival. The year 2011 triggered a new dawn for melanoma therapeutics with two novel agents receiving regulatory approval. With the approval of vemurafenib, a first-in-class inhibitor of BRAF V600E mutant melanoma, and ipilimumab, a first-in-class CTLA-4 inhibitor, we now have two agents that improve survival for patients with this devastating disease. Additionally, several agents are currently in development and hold promise to further advance clinical outcomes for patients.